Pharmacogenetics: Making cancer treatment safer and more effective - Newman, William G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Chemotherapy has made a dramatic difference to improved survival in patients with cancer. However, not all patients respond and some experience serious side effects. "Pharmacogenetics: Making cancer treatment safer and more effective" is an up to date summary of the exciting new field of how genetic testing can tailor more effective prescription in oncology. It is targeted at oncologists and professionals involved in the treatment of patients with cancer. It provides a core background in genetics and pharmacological principles before providing chapters from acknowledged experts in the field on genetic tests in specific cancer types, including breast, bowel and lung cancer. Clinical cases are used to illustrate the practical application of this knowledge. Chapters on ethics, health economics and the industry aspects of pharmacogenetics set out the challenges and opportunities afforded by this new science.
Principles of Cancer Treatment -- Clinical Pharmacology and Anticancer Drugs -- Principles of Genetics and Pharmacogenetics -- Pharmacogenetics in the Management of Breast Cancer -- Pharmacogenetics in Colorectal Cancer -- Pharmacogenetics in Lung Cancer -- Pharmacogenetics and Cancer Treatment in Children -- Pharmacogenetics in Palliative Care -- Genetic Predictors of Normal Tissue Response to Radiotherapy -- Cancer Pharmacogenetics in Industry -- Ethical Issues in Pharmacogenetics -- Economics of Cancer Pharmacogenetics -- Future Advances in Cancer Pharmacogenomics.
Keywords: Medicine; Oncology; Human genetics; Toxicology; Biomedicine; Cancer Research; Pharmacology/Toxicology.; Human Genetics; Oncology; Biomedicine general